ANALISIS KOMUNIKASI INTERPERSONAL ANTARA GURU DAN SISWA DALAM PEMBELAJARAN MATEMATIKA [AN ANALYSIS OF INTERPERSONAL COMMUNICATION BETWEEN TEACHERS AND STUDENTS IN LEARNING MATHEMATICS] - Ndraha, Yanuar Rahmat; Appulembang, Oce Datu (Universitas Pelita Harapan, 2020)
Communication is a representation of God's nature in humans who are created in His image – Imago Dei – and therefore, part of the nature of teachers and students. One form of communication in learning is interpersonal communication. Interpersonal communication helps teachers and students learn and carry out learning, and can fosters students' interest in learning mathematics. Based on the authors’ observations and reflections when teaching at school X, interpersonal communication in learning mathematics was present, but students were still noisy, sleeping, and did not listen to the teacher which resulted in a lack of understanding of the basic mathematical concepts. Based on this, this paper aims to analyze interpersonal communication between teachers and students in learning mathematics. The research methods is a literature review. The results of the analysis show that interpersonal communication fosters students' interest in learning mathematics. The problems that occur are due to a lack of self-confidence, a lack of recognition of students, and less attention to important factors in interpersonal communication. To overcome these three factors, it is necessary to build students’ self-confidence by fostering a positive perception of students' abilities and building a good community with teachers and the existing support system.BAHASA INDONESIA ABSTRACT: Komunikasi merupakan representasi natur Allah dalam diri manusia sebagai Imago Dei. Oleh karena itu, komunikasi merupakan natur dari guru dan siswa. Salah satu jenis komunikasi yang tepat dalam pembelajaran matematika adalah komunikasi interpersonal. Komunikasi interpersonal membantu guru dan siswa dalam belajar dan menjalankan pembelajaran, misalnya, menumbuhkan minat siswa dalam belajar matematika. Hasil observasi dan refleksi mengajar penulis di sekolah X menunjukkan terjadinya komunikasi interpersonal pada pembelajaran matematika, namun siswa masih ribut, tidur, dan kurang mendengarkan guru dalam pembelajaran yang mengakibatkan pemahaman akan konsep dasar matematika kurang. Berdasarkan hal tersebut, tujuan penulisan ini adalah untuk menganalisis komunikasi interpersonal antara guru dan siswa di dalam pembelajaran matematika. Metode penelitian ini adalah kajian literatur. Hasil analisis menunjukkan komunikasi interpersonal menumbuhkan minat belajar siswa terhadap matematika. Hal ini disebabkan karena kurangnya kepercayaan diri, kurangnya pengenalan akan siswa dan kurang memperhatikan faktor-faktor penting dalam komunikasi interpersonal. Untuk mengatasi ketiga faktor tersebut, maka siswa perlu dibangun rasa percaya diri, dengan cara menumbuhkan persepsi positif terhadap kemampuan diri dan membangun komunitas yang baik dengan guru dan support system yang ada.